Current strategies for armoring chimeric antigen receptor T-cells to overcome barriers of the solid tumor microenvironment - Yang, Dorothy D.; Macmorland, William; Arnold, James N. (Frontiers in Immunology, 2025)
Chimeric antigen receptor (CAR) T-cell therapy is a transformative immunotherapeutic approach, yet its application in solid tumors is hindered by the immunosuppressive tumor microenvironment (TME). The TME restricts T-cell trafficking, impairs effector functions, and promotes exhaustion through soluble factors, metabolic stress, and suppressive cell populations. Recent efforts to enhance CAR T-cell efficacy have focused on armoring strategies that ‘reprogram’ and ‘boost’ T-cell responses within the TME. These include engineered expression of dominant-negative receptors or cytokine-releasing constructs (such as IL-12 and IL-18) to reshape the local immune milieu and improve T-cell effector function, synthetic Notch receptors for inducible gene expression, and chemokine receptor knock-ins to improve tumor infiltration. Additional approaches aim to modulate intrinsic metabolic pathways to improve CAR T-cell persistence under hypoxic or nutrient-deprived conditions. Armoring strategies that recruit bystander or endogenous immune cells also activate broader anti-tumor immunity that prevents antigen escape and may induce more durable anti-tumor responses. This review highlights the molecular and cellular mechanisms by which current armoring strategies enhance CAR T-cell functions in solid tumors, offering a perspective on improving immune cell engineering for overcoming the hurdles encountered in deploying these therapies against solid cancers.